From broadband deployment to climate action: Key considerations in the development of climate policies across OECD countries - Sarah Kate Palmer; Joe Rowsell; Stephen Schmidt (International Telecommunications Society (ITS), 2023)
This research paper examines an underexplored facet of climate change mitigation - digital climate policies. Despite empirical evidence demonstrating the potential of broadband networks to substantially reduce greenhouse gas emissions (GHGe), these networks are conspicuously absent from the climate policies of G7 countries. To address this critical omission, the paper investigates three key areas: the countries and sectors with the greatest potential for adopting digital climate policies; the effectiveness of digital climate policies in reducing GHGe under various economic and social conditions; and the barriers hindering the development of such policies. Utilizing a mixed-methods approach, the study aims to provide a comprehensive understanding of the role digital climate policy can play in climate change mitigation, fostering an international community of practice and offering robust data for further empirical research. The findings of this paper hold significant implications for the design and implementation of climate policies in advanced economies.
Keywords: 330; Telecommunications; Broadband; 5G networks; 5G solutions; digitization; telecommunications policy; climate change; digital policy; climate change policy